2020
DOI: 10.1002/ardp.202000366
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of nitrogen mustard anticancer agents with improved cytotoxicity

Abstract: In previous studies, we demonstrated that esters of bendamustine containing a basic moiety are far more cytotoxic anticancer agents than their parent compound and that the substitution of the labile ester moiety by a branched ester or an amide markedly increases stability in the blood plasma. In the current study, we showed that this substitution was bioisosteric. Aiming at increased cytotoxicity, we introduced the same modification to related nitrogen mustards: 6‐isobendamustine, chlorambucil, and melphalan. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…N-mustards—not only M [ 14 ]—played a pivotal role in the development of chemotherapy for cancer [ 40 , 41 , 42 , 43 , 44 , 45 ]. Their development is continuing at a considerable pace [ 46 , 47 , 48 , 49 , 50 , 51 ]. The present study contributes its share to this field.…”
Section: Discussionmentioning
confidence: 99%
“…N-mustards—not only M [ 14 ]—played a pivotal role in the development of chemotherapy for cancer [ 40 , 41 , 42 , 43 , 44 , 45 ]. Their development is continuing at a considerable pace [ 46 , 47 , 48 , 49 , 50 , 51 ]. The present study contributes its share to this field.…”
Section: Discussionmentioning
confidence: 99%
“…(C) According to Antoni and Bernhardt, DCC is used as a coupling reagent for producing bendamustine ester. 11 Since bendamustine is generally given intravenously, there have been a few patent claims for formulations that could be taken orally. Additionally, it has been demonstrated that the esterification process of the carboxylic acid moiety improves the hydrolytic stability of the N-lost moiety (due to many causes), which may increase the likelihood of oral administration.…”
Section: Table 1 Applications Of DCCmentioning
confidence: 99%
“…The bendamustine ester 13 was made with the use of the coupling reagent N , N ′-dicyclohexylcarbodiimide (DCC), and for the synthesis of the new bendamustine amide 14 , the coupling reagents 2-(1 H -benzotriazole-1-yl)-1,1,3,3-tetramethylammonium tetrafluoroborate (TBTU­) and N , N ′-diisopropylethylamine (DIPEA) were consumed. 11…”
Section: Table 1 Applications Of DCCmentioning
confidence: 99%
“…The study was performed using three models of hematological malignancy: RPMI8226 (myeloma cancer cells), THP1 (acute monocytic leukemia cells), and HL60 (promyelocytic leukemia cells). Modification of the carboxyl group by esterification of the compound showed the highest efficacy, and the results indicated that the ester group is necessary to increase the cytotoxic activity of melphalan [ 142 , 143 ]. In vitro studies conducted by this group of researchers showed that new MEL analogues have better antitumor activity than the parent drug.…”
Section: Attempts To Find a “Better Melphalan”mentioning
confidence: 99%